PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN LECTORA INSPIRE TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM (PAI) SISWA KELAS X TKJ DI SMK 17 AGUSTUS 1945 GENTENG - Ahmad Aziz Fanani; Imam Mashuri; Istidadiatul Maghfiroh; Muh. Barid Nizarudin Wajdi (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2021)
This research aims to find out whether there is an influence of the lectora inspire learning media on the learning outcomes of The Tenth Grade Students of TKJ at SMK 17 Agustus 1945 Genteng 2018/2019 Academic Year. This research is a quantitative research and the research method used is a quasi-experimental method. This research was carried out at SMK 17 Agustus 1945. The Objects in this study were students of The Tenth Grade Students of TKJ which contains of 55 students. As a matter of fact, there were only 44 students who takeas a sample. While the method of data collection in this study uses tests, they are pretes tand posttest and documentation used to obtain the information school profile, the educator data and education staff, the students’ list and teachers’ list, study grup, and the school infrastructure. The data analysis uses the T test with the Independent Sample Test formula. The result of test shown that the post test result obtained from the two classes namely thitung -6,215 and ttabel 2,01537. The procure of score shown that thitung < ttabel or -6,215 < 2.01537 with sig tailed 0,000 < 0,05 on the signification stage 95%. Based on the hypothesis variable, Lectora Inspire Learning Media and the variable of learning result The Tenth Grade Students of TKJat SMK 17 Agustus 1945 Genteng, on the significant stage 0,05 shown the significance. So, the variable of the Use of Lectora Inspire Learning Media give positive influence and significant gain the students result at at SMK 17 Agustus 1945Genteng. Thus, Ho is refused and Ha is accepted. So, it can be deduced that there is the significant effect of experiment class and control class.